2011
DOI: 10.1111/j.1600-051x.2010.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides and periodontal disease

Abstract: Aims: The goal of this review is to identify the antimicrobial proteins in the oral fluids, saliva and gingival crevicular fluid and identify functional families and candidates for antibacterial treatment. Results: Periodontal biofilms initiate a cascade of inflammatory and immune processes that lead to the destruction of gingival tissues and ultimately alveolar bone loss and tooth loss. Treatment of periodontal disease with conventional antibiotics does not appear to be effective in the absence of mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(176 citation statements)
references
References 201 publications
2
163
0
11
Order By: Relevance
“…4, 80% and almost 100% of the bacteria were killed by treatment with 5 and 20 μg/mL of LL-37 peptide for 30 min, respectively. LL-37 has been shown to exert antimicrobial activity against oral periodontopathic bacteria, P. gingivalis, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, and Fusobacterium nucleatum (6). It has been reported that LL-37 neutralizes LPS from P. gingivalis and inhibits LPS-induced inflammatory cytokine production (27).…”
Section: Discussionmentioning
confidence: 99%
“…4, 80% and almost 100% of the bacteria were killed by treatment with 5 and 20 μg/mL of LL-37 peptide for 30 min, respectively. LL-37 has been shown to exert antimicrobial activity against oral periodontopathic bacteria, P. gingivalis, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, and Fusobacterium nucleatum (6). It has been reported that LL-37 neutralizes LPS from P. gingivalis and inhibits LPS-induced inflammatory cytokine production (27).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the diverse functional classeswhich include cationic peptides, bacterial agglutination and adhesion, metal ion chelators, peroxidase activity, cell wall activity, and proteolytic inhibitors (Gorr 2009;Gorr and Abdolhosseini 2011)-enhance the antibacterial activity of oral fluids and limit the development of bacterial resistance to endogenous AMPs, although it should be noted that the in vivo function of individual AMPs is not entirely clear and a single AMP may exhibit multiple functions. Several AMPs are found in the oral cavity in concentrations below the experimentally determined minimal inhibitory concentration (MIC), casting some doubt on their antibacterial activity in the oral cavity (Gorr and Abdolhosseini 2011).…”
Section: Amps In the Oral Cavitymentioning
confidence: 99%
“…We hypothesized that the diverse functional classeswhich include cationic peptides, bacterial agglutination and adhesion, metal ion chelators, peroxidase activity, cell wall activity, and proteolytic inhibitors (Gorr 2009;Gorr and Abdolhosseini 2011)-enhance the antibacterial activity of oral fluids and limit the development of bacterial resistance to endogenous AMPs, although it should be noted that the in vivo function of individual AMPs is not entirely clear and a single AMP may exhibit multiple functions. Several AMPs are found in the oral cavity in concentrations below the experimentally determined minimal inhibitory concentration (MIC), casting some doubt on their antibacterial activity in the oral cavity (Gorr and Abdolhosseini 2011). As an example, ß-defensins are found in saliva at concentrations that are 1 to 2 orders of magnitude below the MIC for several oral bacteria, including Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Streptococcus mutans (Gorr and Abdolhosseini 2011 with a dramatic increase in periodontal disease, suggesting that this AMP has a direct effect on the survival of, or susceptibility to, periodontal pathogens (reviewed in Gorr and Abdolhosseini 2011).…”
Section: Amps In the Oral Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, neutrophil defensin-1 exhibits broad-spectrum antimicrobial activity by binding to specific sites on the cell membrane with subsequent release of cellular ATP in the absence of cytolysis [22,23]. The proteins identified in caries-susceptible subjects, like hemoglobin, protein S100-A9, SPLUNC2 and prolactin-inducible protein, may contribute to the host innate immunity in the oral cavity [18,24].…”
Section: Chemicals and Reagentsmentioning
confidence: 99%